2015
DOI: 10.1038/jhg.2015.104
|View full text |Cite
|
Sign up to set email alerts
|

Joint effect of the SMN2 and SERF1A genes on childhood-onset types of spinal muscular atrophy in Serbian patients

Abstract: Spinal muscular atrophy (SMA) is caused by functional loss of the survival of motor neuron 1 (SMN1) gene. Despite genetic homogeneity, phenotypic variability indicates the involvement of disease modifiers. SMN1 is located in 5q13.2 segmental duplication, enriched in genes and prone to unequal rearrangements, which results in copy number polymorphism (CNP). We examined the influence of CNP of 5q13.2 genes and their joint effect on childhood-onset SMA phenotype. Multiplex ligation-dependent probe amplification (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…Despite the absence of association in our study, a recent study by Kano et al [24] reported that the NAIP protein level in ALS patients was lower by nearly half compared to healthy controls. These latest findings and the implication of SERF1 CNVs in the SMA clinical outcome justify research efforts focused on the role of NAIP and SERF1 CNVs in SALS [15].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Despite the absence of association in our study, a recent study by Kano et al [24] reported that the NAIP protein level in ALS patients was lower by nearly half compared to healthy controls. These latest findings and the implication of SERF1 CNVs in the SMA clinical outcome justify research efforts focused on the role of NAIP and SERF1 CNVs in SALS [15].…”
Section: Discussionmentioning
confidence: 72%
“…Since MLPA is a relative quantification technique, all samples were compared with 15 reference samples using the Coffalyser.Net software (MRC-Holland, Amsterdam, the Netherlands). Ratios of MLPA probes specific for 5q13.2 genes and the assigned copy numbers were as previously described [15]. Reproducibility of the MLPA method was determined by running ~30% of randomly selected samples in independent duplicates and by obtaining identical results between the replicas.…”
Section: Genetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients with 4 copies of SMN2 can present with anywhere from type 1 to type 4 disease [27,39]. There are other genetic modifiers of SMA disease severity, such as SERF1A and PLS3 [40][41][42], which further confounds a prediction of disease severity based solely on SMN2 copy number (of note, the role of PLS3 as a modifier of SMA disease severity has not been supported in some mouse models of SMA [43]). Thus, clinical assessment of peak motor function still provides one of the best predictors of disease severity and life expectancy.…”
Section: Variable Severity and Disease Typesmentioning
confidence: 99%
“…34 Razvojem novih metoda za kvantitativno određivanje broja kopija gena pokazano je da između težine kliničke slike i broja genskih kopija SMN2 postoji inverzna korelacija, što pokazuju i rezultati naše studije. 19,23,35,36 Zaključak Ovim istraživanjem uspostavljena je značajna korelacija između broja kopija SMN2 gena i fenotipa SMA pacijenata. Zasigurno je da postoje i drugi faktori koji mogu da utiču na kliničku ekspresiju bolesti, te stoga, uzimajući u obzir njenu genetičku osnovu, sve veću zastupljenost asimptomatskih heterozigotnih nosilaca delecije SMN1 gena u populaciji, ali i činjenicu da još uvek ne postoji adekvatna kauzalna terapija, genetsko testiranje treba da bude ključni korak za dijagnozu ovog neuromišićnog obolenja i za adekvatno genetsko savetovanje.…”
Section: Diskusijaunclassified